The Environmental Implications of Russia's Accession to the World Trade Organization - Böhringer, Christoph (The World Bank, 2014)
This report investigates the environmental impacts of Russia's accession to the World Trade Organization. A 10-region, 30-sector model of the Russian economy is developed. The model is innovative and more accurate empirically in that it contains foreign direct investment, imperfectly competitive sectors, and endogenous productivity effects triggered by World Trade Organization accession along with environmental emissions data in Russia for seven pollutants that are tracked for all 30 sectors in each of the 10 regions. The decomposition analysis shows that despite the fact that World Trade Organization accession allows Russia to import better technologies and reduce pollution from the "technique effect," on balance World Trade Organization accession alone will increase environmental pollution in Russia through a shift toward dirty industries (the "composition effect") and the expansion of output with its associated increase in pollution ("scale effect"). The paper assesses the costs of three types of environmental regulations to reduce carbon dioxide emissions by 20 percent. The paper simultaneously implements a central case scenario with each of the carbon dioxide emission reduction policy initiatives. The analysis finds that the welfare gains of World Trade Organization accession are large enough to pay for the costs of any of the three environmental abatement policies, while leaving a net welfare gain. But the political economy implications are that the non-market-based policies are more costly and the command and control policy, which is not well targeted, is very costly. Based on a constant returns to scale model, the estimated welfare gains are insufficient to finance the costs of environmental regulation